Efektivitas Koagulan Terhadap Penurunan Energi Potensial Pada Pengolahan Air di PDAM Tirta Pakuan Kota Bogor - Pradiani, Wita; Andriana, Hernawan; Suningrat, Asep Yoga (Integrasi : Jurnal Ilmiah Teknik Industri, 2022)
In the processing of raw water into clean water need to add coagulant to remove turbidity when the turbidity exceeds the limit specified requirements. Coagulant commonly used for water treatment that Poly Aluminum Chloride (PAC), Aluminum Sulfate and Ferry Chloride. This study aims to determine the optimum dose of coagulant Poly Aluminum Chloride (PAC), Aluminum Sulfate and Ferry Chloride and to compare its effectiveness in water treatment Cisadane in PDAM Tirta Pakun Bogor with different turbidity levels.Cisadane river water sample taken on different days with different turbidity levels. Determination of the optimum dose of coagulant is done by providing different dosage variations. Test parameter and characteristics of raw ait water jar test result of the test, to test the turbidity mearused by the turbidymeter total dissolved solids mearused by conductometer, pH mearused by pH meter, Fe and Mn measured by spectrophotometer and organic substance using titration method. Then the experimental data obtained were compared with the reqquirements of Permenkes No. 492/Menkes/iv/2010.Of the result obtained optimum dose at low turbidity coagulant Poly Aluminum Chloride (PAC) 30,2 NTU at 14 mg/L and Ferry Chloride at 16 mg/L.. While high turbidity of 681 NTU, the optimum dose for coagulant Poly Aluminum Chloride (PAC) at 35 mg/L, Aluminum Sulfate at 5 mg/L and Ferry Chloride at 40 mg/L. Coagulant more effective water treatment raw cisadane river in the PDAM Tirta Pakuan Bogor is coagulant Poly Aluminum Chloride(PAC). Because Poli Aluminium chloride is more effective in reducing potential energy as a barrier energy in the aggregation process.